2009
DOI: 10.25011/cim.v32i6.10657
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activity of some systemic and topical antihistaminic preparations

Abstract: Purpose: In vitro antibacterial activity of topical and systemic antihistaminic preparations containing different active substrates against the standard strains of two bacteria was evaluated. Methods: Four topical and 3 systemic preparations containing pheniramine maleate, chlorophenoxamine hydrochloride, and diphenhydramine hydrochloride were studied. The antibacterial activities of these preparations against strains of S. aureus (American Type Culture Collection, ATCC 29213) and S. epidermidis (ATCC 25212) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…While other studies have shown an enhancement of antibiotic effects with diphenhydramine against several bacteria [59,60,72,73]. To our knowledge, this is the first demonstration of antibiofilm activity.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…While other studies have shown an enhancement of antibiotic effects with diphenhydramine against several bacteria [59,60,72,73]. To our knowledge, this is the first demonstration of antibiofilm activity.…”
Section: Discussionsupporting
confidence: 48%
“…DPD was shown to have antibacterial effects against S. aureus [59] and may potentiate the effects of levofloxacin against S. aureus or P. aeruginosa [60]. We showed effects of DPD alone against P. aeruginosa at concentrations that activate T2R receptors.…”
Section: Discussionmentioning
confidence: 63%
“…DPD also disrupts P. aeruginosa growth, biofilm production, and cell attachment of both lab and clinical strains. DPD was shown to have antibacterial effects against S. aureus [28] and may potentiate effects of levofloxacin against S. aureus or P. aeruginosa [29]. We show effects of DPD alone against P. aeruginosa at concentrations that activate T2R receptors.…”
Section: Discussionmentioning
confidence: 63%
“…Topical diphenhydramine exerts potent antipruritic, anti-inflammatory, antibacterial and anesthetic effects and reinforces the epidermal barrier function. [91011] Ketamine, a high-affinity antagonist of the glutamate N-methyl-D-aspartate receptor, exerts potent antinociceptive and anesthetic properties by various mechanisms especially stimulation of the γ-aminobutyric acid A receptors,[1213] suppresses the release of proinflammatory cytokines through TLR4/2 inhibition, and mimics the biological effects of LDN. [1314] Table 1 summarizes the biological effects of these agents.…”
Section: Discussionmentioning
confidence: 99%